Do Land Use Policies Follow Road Construction - Miquel-Àngel Garcia-López; Albert Solé-Ollé; Elisabet Viladecans Marsal (Center for Economic Studies and ifo Institute (CESifo), 2014)
We study whether local land use policies are modified in response to enhanced demand for building generated by a new highway, and examine the extent to which this effect of land use regulations affects building activity. We focus on the case of Spain during the last housing boom (1995-2007). We assembled a new database with information about new highway segments and the modification of the land zoning status in nearby municipalities. The empirical strategy compares the variation in the amount of developable land before-after the construction of the highway in treated municipalities and in control municipalities with similar pre-treatment traits. Our results show that, following the construction of a highway, municipalities converted a huge amount of land from rural to urban uses. We also show that new highways have an impact on building activity.
Keywords: R40; R52; O20; 330; land use regulation; highways